Mindfulness‐based cognitive therapy (MBCT) is cost‐effective compared to a wait‐list control for persistent pain in women treated for primary breast cancer—Results from a randomized controlled trial. Issue 12 (31st May 2017) - Johannsen, M.; Sørensen, J.; O'Connor, M.; Jensen, A.B.; Zachariae, R.
Abstract: Objective: To investigate the cost‐effectiveness of mindfulness‐based cognitive therapy (MBCT) compared to a wait‐list control group for pain in women treated for breast cancer. Methods: A total of 129 women were randomly allocated to MBCT or a wait‐list control group. The primary outcome was the minimal clinically important difference (MCID) on pain intensity (≥2 point reduction on an 11‐point Numeric Rating Scale). Analyses were conducted from the health care system perspective and included data on health care utilization and pain medication retrieved from national registries for the period from baseline (T1) to 6 months postintervention (T4). Bootstrap simulations were used to estimate confidence intervals for the incremental cost and effect measures, and cost‐effectiveness acceptability curves. In sensitivity analyses, we replaced dropouts with last‐observation‐carried‐forward and tested consequences of higher costs of the intervention. Results: The intervention cost was 240€ per participant. The average total cost from T1 to T4 in the MBCT group was 1706€ compared with 2436€ in the control group (mean difference: 729€, P  = .07). More women in the MBCT group (N:19/36; 52.8%) than in the control group (N:14/48; 29.2%) achieved an MCID in pain intensity (OR=2.71, P  = .03). The MBCT was cost‐effective with a probability of 85% with a value of an additional women achieving MCID set to zero remained cost‐effective with a probability of 70% to 82% when smaller effect and higher MBCT costs were assumed. Conclusions: Our results suggest that MBCT is a cost‐effective pain intervention for women treated for breast cancer. Future studies could include utility measures, indirect costs, and active control groups to increase the generalizability and pragmatic value of the results.